The Dialectic Between the Fiqh of Tolerance and Human Rights in the Context of Religious Pluralism: The Indonesian Experience - Nur Chanifah (Pustaka Peradaban, 2025)
Indonesia is characterized by profound religious diversity encompassing multiple religions, beliefs, and religious practices. While such plurality has the potential to function as social capital for strengthening national cohesion, recent decades have witnessed a significant rise in religion-based intolerance, including the rejection of houses of worship, the dispersal of minority religious activities, and various forms of social intimidation. These developments indicate persistent structural and normative deficiencies in the governance of freedom of religion or belief (FoRB) in Indonesia. This article critically examines the relationship between religious plurality, practices of intolerance, and weaknesses in the governance of FoRB, while proposing a more progressive normative alternative. Employing a qualitative dialectical analysis based on document review and literature studies, the study maps the patterns and actors of religious intolerance and reassesses the normative foundations of religious governance through the integration of the fiqh of tolerance and human rights principles. The findings demonstrate that the escalation of intolerance is driven not only by regulatory weaknesses and majoritarian bias but also by exclusive religious interpretations that are misaligned with constitutional values and international human rights standards. This study argues that reconstructing an inclusive normative framework—grounded in a dialectical engagement between fiqh of tolerance and human rights—is essential for strengthening the protection of religious minorities and fostering social cohesion in Indonesia. Indonesia dicirikan oleh keberagaman agama dan kepercayaan yang kompleks, yang secara teoretis merupakan modal sosial bagi kohesi nasional. Namun, meningkatnya praktik intoleransi dalam beberapa dekade terakhir—seperti penolakan rumah ibadah dan intimidasi terhadap kelompok minoritas—mengindikasikan adanya persoalan struktural dan normatif dalam tata kelola Kebebasan Beragama dan Berkeyakinan (KBB/FoRB). Artikel ini bertujuan menganalisis hubungan dialektis antara pluralitas keagamaan, praktik intoleransi, dan kelemahan tata kelola KBB di Indonesia, serta menawarkan kerangka normatif alternatif yang progresif. Menggunakan metode kualitatif melalui analisis dialektis berbasis studi literatur, penelitian ini memetakan pola serta aktor intoleransi, sekaligus meninjau kembali fondasi pengelolaan kehidupan beragama melalui integrasi konsep fiqh toleransi dan prinsip Hak Asasi Manusia (HAM). Temuan penelitian menunjukkan bahwa eskalasi intoleransi dipicu oleh bias mayoritarian dalam regulasi serta tafsir keagamaan eksklusif yang tidak selaras dengan nilai konstitusional dan standar HAM internasional. Artikel ini menyimpulkan bahwa rekonstruksi kerangka normatif yang inklusif—melalui dialektika fiqh toleransi dan HAM—merupakan prasyarat krusial untuk memperkuat perlindungan kelompok minoritas dan menciptakan kohesi sosial yang berkelanjutan di Indonesia.